1980
DOI: 10.1111/j.1095-8649.1980.tb02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Some physiological consequences of angling stress in muskellunge, Esox masquinongy Mitchill

Abstract: Capture of muskellunge by angling resulted in a reduction of blood pH, elevated lactic acid concentrations, and a drop in total carbon dioxide and bicarbonate concentrations. The acidaemia was most severe immediately after capture and began to decline well before the blood lactate levels rose. Blood lactate levels were not as high as those characterizing fatigue in most other species. Recovery from the acidosis required 12 to 18 h and was accompanied by declines of 22% and 4Ou/o in haemoglobin and haematocrit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 26 publications
1
42
5
Order By: Relevance
“…Adult muskellunge were collected by electroshocking during September 2001 and 2002 from , 1980-1999Muskies, Inc.) Deer Lake, Polk County, in northwestern Wisconsin. Deer Lake has a high density of adult muskellunge (0.94/surface acre ‡76 cm (30 in); Margenau and AveLallemant 2000) and is maintained by stocking (WDNR 1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult muskellunge were collected by electroshocking during September 2001 and 2002 from , 1980-1999Muskies, Inc.) Deer Lake, Polk County, in northwestern Wisconsin. Deer Lake has a high density of adult muskellunge (0.94/surface acre ‡76 cm (30 in); Margenau and AveLallemant 2000) and is maintained by stocking (WDNR 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Large muskellunge ‡76 cm (30 in) are difficult to handle and to subsequently remove a hook. In addition, large muskellunge may be exposed to additional stress as an angler attempts to determine if the fish exceeds a minimum length and handles the fish to photograph the catch (Beggs et al 1980). The paucity of data on large muskellunge is due to low sample sizes and sparse populations.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear if and how the behaviour of pike is altered immediately following capture and when resumption of normal behaviour occurs. Another limitation from previous studies on physiological disturbance and recovery in pike is that they all focused solely on exercise (Soivio and Oikari, 1976;Beggs et al, 1980;Schwalme and Mackay, 1985b), and only the study by Schwalme and Mackay (1985a) actually involved a real angling event. It is unclear the degree to which the pike's physiological disturbances to angling-related stressors in laboratory setting are also expressed in real life angling situations in field settings.…”
Section: Introductionmentioning
confidence: 92%
“…Even though larger esocids, specifically trophy fish, may be at risk because of angling-associated exhaustion and sublethal stress (Miles et al 1974;Beggs et al 1980), smaller fish may be less prone to these negative consequences when bait is actively fished. Our results suggest the incidental bycatch of small muskellunge that may occur in some fisheries will probably result in null or inconsequential effects on a fishery if anglers employ strategies whereby baitfish are not swallowed by muskellunge before the hook is set.…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, several catch-and-release studies have concluded that muskellunge experience stress (Miles et al 1974;Beggs et al 1980) and physical injury that can lead to mortality (Gasbarino 1986). Although catch-and-release mortality and sublethal effects are contentious topics in most recreational fisheries (Cooke and Suski 2005), they are still important to examine, particularly for long-lived species (Schroeder and Love 2002) such as muskellunge.…”
mentioning
confidence: 99%